Identidade psicossocial dos adolescentes no regime de internato na Educação Agrícola - Morais, Alessandra Xavier de; Benelli, Sílvio José [UNESP]; Monteiro, Rosa Cristina (My University, 2013)
Psychosocial Identity of the adolescents in boarding school system in the agricultural education Abstract: This article is the result of a research where we try to study and to understand the psychosocial identity of adolescents undergoing boarding. We discussed the issue of boarding school in literature and notes about adolescence in various psychological approaches. Research strategies were interviews, and focus group reports. We conclude that, even with the difficulties students believe that the promising future can only be achieved through technical training, which would enable them not only to acquire a knowledge, but also as a way to gain access to a better-paying job. A better understanding of the surrounding reality allows us to subsidize various professional institutions also adopt boarding as an option to stay.

Este artigo é o resultado de uma pesquisa de mestrado onde procuramos estudar e compreender a identidade psicossocial dos adolescentes submetidos ao regime de internato. Discutimos o tema do colégio interno na literatura além de apontamentos sobre adolescência em diversas abordagens psicológicas. As estratégias de investigação foram entrevistas, relatos e grupo focal. Concluímos que, mesmo com as dificuldades os alunos acreditam que o futuro promissor só pode ser alcançado através de uma formação técnica, o que lhes possibilitaria não só adquirirem um saber, mas também como forma de terem acesso a um trabalho de melhor remuneração. Um melhor entendimento da realidade circundante permite que possamos subsidiar diferentes profissionais de instituições que também adotam o internato como opção de permanência.
Keywords: School boarding; Agricultural education; Psychosocial identity; Internato Escolar; Educação agrícola; Identidade psicossocial